Social Dynamics of Elementary School Students: The Impact of TikTok in the Digital Age - Yayan Alpian; Sri Wulan Anggraeni; Ayu Fitri; Putri Nur Rizki (Jurnal Ilmiah Sekolah Dasar, 2024)
Social media, especially TikTok, has become an inseparable part of the lives of elementary school students in Indonesia, causing a shift in their social dynamics. The main aim of this research is to analyze and evaluate the impact of using TikTok on the transformation of elementary school students' social attitudes through an in-depth assessment of changes in students' behavior and interpersonal interactions. This research uses a qualitative descriptive method. Involving 21 students, one teacher, and one student's parent, data collection techniques were carried out using interviews and observations and analyzed using four steps, namely data collection, data reduction, presentation, and drawing conclusions/verification. The research results show that the use of TikTok causes students to come to school late, affects learning motivation, and changes social interaction patterns, changes students' language and behavior, hinders communication ethics and social norms. Parent and teacher responses highlight concerns over TikTok's influence, although oversight challenges remain. In conclusion, a concerted effort is needed to guide the use of TikTok to support children's holistic development socially, emotionally and academically in the digital era. This research contributes to a deeper understanding and guidance for wise social media use among elementary school students.